Wetland Environment Deteritorialization In The Perspective Of Political Ecology In Banjar District - Abdurrahman Abdurrahman; M Najeri Al Syahrin; Egi Vadia; Nahriatul Salsabella; Alma Rajab (International Journal of Politic, Public Policy and Environmental Issues, 2021)
Conflict of land conversion (deterritorialization) is an ecological crisis that continues to reproduce in the domination space of the capitalist economy and goes hand in hand with the use of the pretext of industrialization and massive scale state political policies. Banjar Regency is geographically located in a strategic area between the cities of Banjarmasin and Banjarbaru. So that it functions as a buffer zone and a center for settlement development and economic activity. This study aims to discover the concept of territorialization of wetlands that exist in the community and respond to the dynamics of the expansion of land conversion (deterritorialization of the wetland environment), whether carried out by corporations, the government, or by the community itself through the tendency of policies that are mechanistic pragmatic. This research uses a qualitative approach, which is considered the most capable of accommodating the dialectical analysis of subjectivity-objectivity accompanied by critical analysis to uncover the problem of deterritorialization of the wetland environment of political ecology in Banjar Regency. Data collection using literature studies and field data collection through FGD, interviews, and observations using the live-in model. It is hoped that the analysis of this research will be able to provide novelty to a philosophical perspective on natural resource management, particularly concerning the environmental functions of wetlands, including swamps and peat areas. Stakeholders and actors engaged in related sectors are also expected to unravel the unequal power relations between actors based on the paradigm of justice and sustainability, accompanied by efforts to overcome various systemic obstacles, anthropocentric obstacles, and local government “bureaucratic dysfunction,” which will be elaborated, comprehensively in this research.